Features of Microbiocenoses of Various Biotopes in Women as Potential Miscarriage Risk Factor - A. E. Goncharov; S. V. Rischuk; B. I. Aslanov; E. A. Lebedeva; D. V. Azarov; A. S. Mokhov; Yu. A. Artemova; M. V. Tabolkina; A. A. Meltser; T. V. Osmirko; A. V. Tushina (Эпидемиология и вакцинопрофилактика)
Relevance. Miscarriage is one of the most common obstetric pathologies that determine the spontaneous death of the fetus. The role of changes in the microbiome of various biotopes is considered as a risk factor of this disease.Aim of the research is to assess the microbiocenoses structure of the reproductive system and the intestine associated with the development of spontaneous miscarriages in early pregnancy.Materials and methods. A case-control study was conducted and organized. The group of «cases» included 23 women with spontaneous miscarriage at 5–14 weeks of pregnancy and the control group included 23 women with normal pregnancies Based on the data of metagenomic sequencing of V3–V4 regions of the 16S rRNA gene, a comparative assessment of the structure of the vaginal and intestinal microbiome in these groups was carried out.Results. As a result of the study, a number of taxonomic groups of microorganisms in the vagina and intestines associated with miscarriage. It was found that the decrease in the proportion of Lactobacillus spp. in the structure of the vaginal microbiome, less than 90% of the total number of identified taxa is associated with this pathology (OR = 5.28 (95% CI = 1.2-23.2)). The gut microbiocenoses of women with spontaneous miscarriage are characterized by less taxonomic diversity than the gut microbiome of women with advanced pregnancy. At the same time, some representatives of the intestinal microbiome (Akkermansia sp., Faecalibacterium sp., Bifidobacterium sp., Methanobrevibacter sp., Lactococcus sp.) predominate in women with a normal pregnancy.Conclusion. The study demonstrated a significant role of changes in microbiocinosis of the reproductive tract and intestines in miscarriage. There is a potentially protective function of lactobacilli. The obtained data substantiates the need for active use of molecular genetic methods focused on the assessing the structure of the vaginal and intestinal microbiota in assessing the risks of reproductive failures.